5-HT6 receptor agonism facilitates emotional learning - Pereira, Marcela; Martynhak, Bruno; Andreatini, Roberto; Svenningsson, Per (Frontiers in Pharmacology, 2015)
Serotonin (5-HT) and its receptors play crucial roles in various aspects of mood and cognitive functions. However, the role of specific 5-HT receptors in these processes remains to be better understood. Here, we examined the effects of the selective and potent 5-HT6 agonist (WAY208466) on mood, anxiety and emotional learning in mice. Male C57Bl/6J mice were therefore tested in the forced swim test (FST), elevated plus-maze (EPM), and passive avoidance tests (PA), respectively. In a dose-response experiment, mice were treated intraperitoneally with WAY208466 at 3, 9, or 27 mg/kg and examined in an open field arena open field test (OFT) followed by the FST. 9 mg/kg of WAY208466 reduced immobility in the FST, without impairing the locomotion. Thus, the dose of 9 mg/kg was subsequently used for tests of anxiety and emotional learning. There was no significant effect of WAY208466 in the EPM. In the PA, mice were trained 30 min before the treatment with saline or WAY208466. Two separate sets of animals were used for short term memory (tested 1 h post-training) or long term memory (tested 24 h post-training). WAY208466 improved both short and long term memories, evaluated by the latency to enter the dark compartment, in the PA. The WAY208466-treated animals also showed more grooming and rearing in the light compartment. To better understand the molecular mechanisms and brain regions involved in the facilitation of emotional learning by WAY208466, we studied its effects on signal transduction and immediate early gene expression. WAY208466 increased the levels of phospho-Ser845-GluA1 and phospho-Ser217/221-MEK in the caudate-putamen. Levels of phospho-Thr202/204-Erk1/2 and the ratio mature BDNF/proBDNF were increased in the hippocampus. Moreover, WAY208466 increased c-fos in the hippocampus and Arc expression in both hippocampus and prefrontal cortex (PFC). The results indicate antidepressant efficacy and facilitation of emotional learning by 5-HT6 receptor agonism via mechanisms that promote neuronal plasticity in caudate putamen, hippocampus, and PFC.